Optimization of geometrical parameters aerodynamic design aircraft articulated tandem with wings - Кузьменко, О.В. (Proceedings of National Aviation University (archive), 2006)
The features of a task of optimization of the plane with unmanned completely wing are considered the existing approaches the block diagram of mathematical model of the plane with unmanned completely wing is given in the decision of similar tasks.